بنية حوض القش ومناخه دراسة في الهيدرولوجيا التطبيقية - سلوم, جوليت (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هذا البحث محاولة لدراسة الظروف البنيوية, والمناخية, والهيدرولوجية في حوض نهر القش, الممتد في المنطقة المدارية ذات المناخ المتوسطي. وقد اعتُمد في دراسة الخصائص المناخية, والهيدرولوجية على المعطيات المأخوذة من محطات الرصد المناخية الواقعة في الجزء الشمالي من المنطقة الساحلية السورية أي "المحطات الميترولوجية في بوقا, والحفة, وصلنفة". هذا العمل واحداً من الأعمال التي ستسهم في تطوير الموارد المائية التي تعد من أهم الموارد الطبيعية في الحوض المدروس. This research tries to study the structure, climate and hydrological conditions of Alkash basin, which lies in the moderate zone with the Mediterranean climate. Climatic and hydrologic characteristics of Al Kash basin are based on materials of observations of the hydrometeorological network in the northern part of the coastal region of Syria (the meterological stations of Bouka, Haffeh, and Slonfieh). This work would be useful in the development of water resources, which are considered as one of the most important natural resources in the basin .